2018
DOI: 10.1039/c8sm00149a
|View full text |Cite
|
Sign up to set email alerts
|

Probing nano-scale viscoelastic response in air and in liquid with dynamic atomic force microscopy

Abstract: We perform a comparative study of dynamic force measurements using an Atomic Force Microscope (AFM) on the same soft polymer blend samples in both air and liquid environments. Our quantitative analysis starts with calibration of the same cantilever in both environments. Intermodulation AFM (ImAFM) is used to measure dynamic force quadratures on the same sample. We validate the accuracy of the reconstructed dynamic force quadratures by numerical simulation of a realistic model of the cantilever in liquid. In sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…We use LDPE as a test sample to determine the accuracy of the method for measuring the Young's modulus of polymers. 10,23 This sample has a nominal Young's modulus of 0.1 GPa. Unfortunately, there is no equivalent test sample to calibrate the viscosity coefficient.…”
Section: Bimodal Am-fm Of the Polymer (Ldpe)mentioning
confidence: 99%
See 1 more Smart Citation
“…We use LDPE as a test sample to determine the accuracy of the method for measuring the Young's modulus of polymers. 10,23 This sample has a nominal Young's modulus of 0.1 GPa. Unfortunately, there is no equivalent test sample to calibrate the viscosity coefficient.…”
Section: Bimodal Am-fm Of the Polymer (Ldpe)mentioning
confidence: 99%
“…The understanding, characterization and mapping of the viscoelastic properties of soft matter at the nanoscale level is an active area of research in polymer science, nanolithography, mechanobiology and force microscopy. [1][2][3][4][5][6][7][8][9][10][11][12] The development of novel nanolithographies demands a fast and high resolution characterization of the viscoelastic properties of polymer resists. 12,13 In mechanobiology, there is some evidence that supports the influence of the cell's viscoelastic processes in its physiology.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not straightforward to extract and quantify standard nanomechanical properties of the samples, and for this reason, multi-frequency methods were developed, where the viscous and elastic response of the sample can be separated. [24][25][26][27] Since multi-frequency methods are able to distinguish between viscous and elastic contributions, they are well-suited for characterizing soft and viscoelastic samples, such as hydrogels. However, these methods rely on a high quality factor of the cantilever to obtain reliable results.…”
Section: Introductionmentioning
confidence: 99%
“…28 This is a limitation when the measurements should be conducted in aqueous media, even though it was recently demonstrated that the intermodulation AFM method can be successfully applied to measure and map tip-surface interactions in water. 27 Lateral force measurements, related to the friction properties, of hydrogels have been studied at the macroscale using different methods. [29][30][31] At the microscale, the colloidal probe AFM method has been applied to study friction properties of poly-HEMA, 32 cartilage 33 and other soft materials.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the plastic deformation, there is another factor that hampers obtaining the true elastic modulus of a sample, i.e., the effect of viscoelasticity [50]. Such viscous response, in many cases, dominates over the elastic response and should be identified separately if we want to obtain a meaningful contact modulus value from the measurements.…”
Section: Evaluation Of the Viscoelastic Contributionmentioning
confidence: 99%